From the History of International Economic, Industrial and Political Relations between Kazakhstan and Russian Federation (1991-1998) - KARASAYEV, Gani M.; YENSENOV, Kanat A.; ALDABERGENOV, Krykbai M.; ZHUMAGULOV, Bolat S.; AMINOV, Talgatbek M. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
In the era of globalization impact of the close relations between the countries in the political, economic, and other directions is important in the world development. From this point of view, within the first few years after the collapse of the Soviet Union, the relations between the immediate neighbors of Kazakhstan and the Russian Federation were formed and developed in all directions. The purpose of the article is to explore the peculiarities of relations between Kazakhstan and the Russian Federation. Geopolitics also plays a key role in the location of the two countries in the valley of Eurasia. The implementation of all conditions based on the partnership between the two countries is beneficial for Kazakhstan and the Russian Federation, which are located in different regions of the world, to establish mutually beneficial contacts in all directions. The study found that the results of international relations between Russia and Kazakhstan are multilateralism, various agreements, joint actions and mutual understanding in the main directions, arrangements and concrete actions for the solution of important issues. Proposed in 1994, by the President of Kazakhstan N.A. Nazarbayev the issue of the Eurasian Union is currently determining its relevance and yielding true results. The history of relations between Kazakhstan and the Russian Federation in the 90s of the ХХ century is based on valuable state documents and scientific data.